2022
DOI: 10.3390/d14070538
|View full text |Cite
|
Sign up to set email alerts
|

Mitochondrial Genomes of two Lycosa spiders (Araneae, Lycosidae): Genome Description and Phylogenetic Implications

Abstract: We sequenced the complete mitochondrial genomes of Lycosa shansia, and Lycosa singoriensis by combining Sanger and next-generation sequencing methods and analyzed the sequenced genomes in order to explore the phylogenetic placement and the mitogenome composition and evolution of these species. The mitochondrial genome of L. shansia was 14,638 bp, whereas that of L. singoriensis was 13,686 bp. The type of genes and direction of the coding strand present in the mitogenomes were the same as those in other species… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 50 publications
2
5
0
Order By: Relevance
“…According to the genomic data of prior research, the phylogenetic relationship of Thomisidae, Oxyopidae, Pisauridae, and Lycosidae could be presented as ((Thomisidae + Oxyopidae) + (Pisauridae + Lycosidae)) (Fernández et al 2018). However, our findings showed that the phylogenetic relationship was presented as (Thomisidae + (Oxyopidae + (Pisauridae + Lycosidae))), which is supported by numerous studies (Li et al 2021; Pons et al 2019; Ye et al 2022). Within Lycosidae, the phylogenetic relationships of three spiders were presented as ( Pirata subpiraticus + ( P. pusiola + P. laura )).…”
Section: Resultssupporting
confidence: 88%
See 4 more Smart Citations
“…According to the genomic data of prior research, the phylogenetic relationship of Thomisidae, Oxyopidae, Pisauridae, and Lycosidae could be presented as ((Thomisidae + Oxyopidae) + (Pisauridae + Lycosidae)) (Fernández et al 2018). However, our findings showed that the phylogenetic relationship was presented as (Thomisidae + (Oxyopidae + (Pisauridae + Lycosidae))), which is supported by numerous studies (Li et al 2021; Pons et al 2019; Ye et al 2022). Within Lycosidae, the phylogenetic relationships of three spiders were presented as ( Pirata subpiraticus + ( P. pusiola + P. laura )).…”
Section: Resultssupporting
confidence: 88%
“…Within Lycosidae, the phylogenetic relationships of three spiders were presented as ( Pirata subpiraticus + ( P. pusiola + P. laura )). These results are well supported by previous spider phylogenetic research and reveal that the mitogenome is a useful tool for uncovering the phylogenetic relationships of spiders (Wheeler et al 2017; Ye et al 2022).…”
Section: Resultssupporting
confidence: 85%
See 3 more Smart Citations